Performance Analysis of the Differences Restricted Access Window (RAW) on IEEE 802.11ah Standard with Enhanced Distributed Channel Access (EDCA) - Doan Perdana; Mulki Nurullah Perbawa; Yoseph Gustommy Bisono (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
IEEE 802.11 standard is a WLAN (Wireless LAN) standard that has been used in all over the world. IEEE 802.11ah is the newer technology that designed to supports Internet of Things (IoT) and Machine-to-machine Communication (M2M). IEEE 802.11ah has a feature called Restricted Access Window (RAW) that capable to reduce power usage and have satisfying Quality of Service (QoS). In this research, Enhanced Distributed Channel Access (EDCA) is also applied. Same as RAW, EDCA also be able to affect QoS by modified the MAC Layer in 802.11 standard. This research used 3 different scenarios for RAW parameters: Modifying the number of RAW Group, Modifying the number of RAW Slot, and Comparing 2 Datamode. The EDCA Parameters that used in this research were: Contention Window and Arbitrary inter-frame Spacing Number. The values that expected to be the output in this research are: Delay, Throughput, Packet Delivery Ratio, Availability, and Reliability. After the research has been simulated, the results are: First, the lowest of average delay was Ngroup = 1, the highest of PDR was Ngroup = Nsta/2, and the highest of Throughput was Ngroup = Nsta/2. Second, the lowest of average delay was RAW Slot = 6, the highest of PDR were RAW Slot = 3 and 4, and the highest of Throughput was RAW Slot = 4. Third, the lowest of average delay was Datamode 3,9 Mbps BW 2 MHz, the highest of PDR was Dat mode 3,9 Mbps BW 2 MHz, and the highest of Throughput was Datamode 3,9 Mbps BW 2 MHz. Reliability, Availability, and Energy Consumption also can be affected by modifying RAW parameters, in 802.11ah Energy Consumption can be reduced by increasing the number of RAW Stations and RAW Groups.